Thirty-eight years of training distribution in Olympic speed skaters - Orie, J.; Hofman, N. (International Journal of Sports Physiology and Performance, 2014)
During the last decade discussion about training-intensity distribution has been an important issue in sports science. Training-intensity distribution has not been adequately investigated in speed skating, a unique activity requiring both high power and high endurance. Purpose: To quantify the training-intensity distribution and training hours of successful Olympic speed skaters over 10 Olympiads. Methods: Olympic-medal-winning trainers/coaches and speed skaters were interviewed and their training programs were analyzed. Each program was qualified and quantified: workout type (specific and nonspecific) and training zones (zone </=1 2 mMol/L lactate, zone 2 2-4 mMol/L lactate, zone 3 lactate >4 mMol/L). Net training times were calculated. Results: The relation between total training hours and time (successive Olympiads) was not progressive (r = .51, P > .5). A strong positive linear relation (r = .96, P < .01) was found between training distribution in zone 1 and time. Zones 2 and 3 both showed a strong negative linear relation to time (r = -.94, P < .01; r = -.97, P < .01). No significant relation was found between speed skating hours and time (r = -.11, P > .05). This was also the case for inline skating and time (r = -.86, P > .05). Conclusions: These data indicate that in speed skating there was a shift toward polarized training over the last 38 y. This shift seems to be the most important factor in the development of Olympic speed skaters. Surprisingly there was no relation found between training hours, skating hours, and time.